The problem of refugees as a factor of active citizenship of inhabitants of Zielona Gora = Problem uchodźców jako czynnik aktywności obywatelskiej mieszkańców Zielonej Góry - Narkiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the issue of civic activity of Poles, as illustrated by the case of Zielona Gora citizens, in reference to the problem of accepting refugees from Syria and other countries at war. The first part of the article presents statistical data on civic activity of Poles which is followed by an attempt of interpreting the presented results in historical and demographic context.
Keywords: uchodźcy; debata publiczna; aktywność obywatelska; refugees; public debate; civic activity